Geographic Information System for Spatial Utilization Licensing of Tabalong Regency Based on Web and Mobile Applications - Radliya, Nizar Rabbi; Wibawa, Julian Chandra; Rabbi, A R (International Journal of Research and Applied Technology (INJURATECH), 2024)
The management of spatial use permits aims to prevent negative impacts on the environment due to spatial use that is not in accordance with the regulations in the regional spatial plan. Currently, in Tabalong Regency, several violations of aaaaa aaa aaspatial use do not match its designation. In order to minimize the occurrence of violations of spatial planning, it is necessary to strengthen control over spatial use through the development of information systems. This study aims to adopt the use of information and communication technology for space utilization permits in the form of implementing the geographic information system concept using the web and mobile-based application media. This study used a qualitative approach through descriptive methods to explore the urgency of geographic information systems as an instrument of utilization control. The results of the study show that the information system application developed is a means for the community, business actors, investors who plan to submit applications related to space utilization permits. This research also produces information system products that can realize transparency of spatial information and control processes of space utilization that can minimize the potential for deviation from procedures and results of licenses issued.